2005
DOI: 10.1097/01.phm.0000151944.22116.5a
|View full text |Cite
|
Sign up to set email alerts
|

Balance, Mobility, and Falls Among Community-Dwelling Elderly Persons

Abstract: Our intervention can improve functional performance and protect against falls and fall-related injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
1
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 26 publications
2
85
1
12
Order By: Relevance
“…However, the effectiveness of these exercise programs as a means of fall prevention in older adults has been controversial. Some studies have demonstrated that exercise prevents falls [9][10][11][12][13][14] , but other studies have shown no effect [15][16][17] . Recently, there has been growing interest in the use of Tai Chi (TC) as an exercise for improving postural balance and prevent falling among older people [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of these exercise programs as a means of fall prevention in older adults has been controversial. Some studies have demonstrated that exercise prevents falls [9][10][11][12][13][14] , but other studies have shown no effect [15][16][17] . Recently, there has been growing interest in the use of Tai Chi (TC) as an exercise for improving postural balance and prevent falling among older people [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…This purpose was fulfilled on the common distance in the often conducted gait analysis distance. A course with different stations, which needs substantial space and material, has only limited applicability [22,23,29] though it might provide a greater understanding, especially when information is separated for the different obstacles and surfaces. Another key aspect is to enlarge the measured gait parameters by wearable systems [8,12,34].…”
Section: Discussionmentioning
confidence: 99%
“…Madureira et al have shown that balance training program is effective in reducing the risk of falling in elderly [16]. Traditionally exercise programs were delivered in a class situation or individually by professional physical therapist [18,19].…”
Section: Related Workmentioning
confidence: 99%